1993
DOI: 10.4141/cjas93-014
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of dietary ascorbic acid supplement on hens subjected to ochratoxin A toxicosis under normal and high ambient temperatures

Abstract: The results suggest that some of the detrimental effects of OA in the diet of the laying hen can be counteracted by dietary supplementation of AA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…At 4 ppm OTA, mortality increases dramatically [134,135]. Haazele et al [139] have demonstrated that vitamin C has beneficial effects in hens exposed to OTA. For the related mycotoxin CIT, which is frequently found as a cocontaminant of food sources [140][141][142], the LD 50 depends on animal strain and sex and on the route of administration.…”
Section: Ota In Human Milkmentioning
confidence: 99%
“…At 4 ppm OTA, mortality increases dramatically [134,135]. Haazele et al [139] have demonstrated that vitamin C has beneficial effects in hens exposed to OTA. For the related mycotoxin CIT, which is frequently found as a cocontaminant of food sources [140][141][142], the LD 50 depends on animal strain and sex and on the route of administration.…”
Section: Ota In Human Milkmentioning
confidence: 99%
“…The ascorbic acid supplementation (300 mg/kg) of laying hen diet that contained 3 ppm OTA has been reported to have a good protective effect against OTA-action and can partially ameliorate OTA-toxicity (including the negative effect of OTA on the eggs production and on the weight of the eggs) [99, 100]. The mechanism of the protective effect is not clear but it is supposed to affect the production of lipid peroxides by OTA and to improve the membrane integrity of cell organelles, which is always affected by OTA-action [22].…”
Section: Methods Of Prophylaxis and Various Preventive Measures Inmentioning
confidence: 99%
“…Also, antipermeability and vasoconstrictive effects of water extract of artichoke could decrease oedema in various internal organs provoked by OTA [18, 27, 29, 30, 94]. The high content of calcium and vitamin C in the steam extract probably has also a protective effect against OTA-toxicity via improving membrane integrity of cell organelles and skeleton-strength of the chicks or via some other ways [27, 29, 94], since some authors reported that ascorbic acid supplementation (300 mg/kg) of laying hen diet that contained OTA (3.0 mg/kg) partially reduced OTA-toxicity [100]. …”
Section: Methods Of Prophylaxis and Various Preventive Measures Inmentioning
confidence: 99%
“…At the 4 ppm level, mortality rate increases dramatically (Gibson et al , 1990. Haazele et al (1993) demonstrated that vitamin C has bene®cial eOE ects in hens exposed to OTA. The LD 50 of citrinin depends on animal strain and sex and on the route of administration.…”
Section: Summary Of the Toxic Eoe Ects Of Ota And Citrininmentioning
confidence: 99%